Eating attitude among adolescents in selected college - K.SILAMBUSELVI,; M.RAMYA RATHI DEVI,; M.HEMAMALINI, (International Journal of Pharma and Bio Sciences, 2017)
Adolescents frequently develop eating disorders and have major public health impact . Screening for eating disorders helps in early identification and earlier treatment. This study was conducted in SRM College of Nursing, Kattankulathur. Quantitative approach and Descriptive Cross sectional design was adopted for the present study. The sample size includes 160 adolescents who were studying B.sc Nursing in SRM College of Nursing. Non-probability Purposive sampling technique was adopted to select the samples for the study. The study variable includes eating attitude whereas the demographic variables includes age, gender, type of family, dietary pattern, religion, Mothers education and family monthly income. 5 point rating scale was used to assess the eating attitude among adolescents. The reliability of the tools was established by split half method for eating attitude scale. The results of the study revealed that 84.4% of the adolescents reported good eating attitude, none of them reported poor and very poor eating attitude. No significant association was observed between the eating attitude and the demographic variables of adolescents. The study concluded that adolescents have good eating attitude and are more sentient about their health and importance of taking proper nutrition.